Planning and Public Relations Strategies at Islamic Elementary School as Efforts to Improve Educational Quality - Ningrum, Intan Kusuma; Arifah, Umi; Ngatiqoh, Siti; Kurniawan, Benny; Fatimah, Siti (Asian Journal of Applied Education (AJAE), 2025)
This research aims to describe the planning and public relations strategies at MI Nurul Huda Sawangan. This research uses a descriptive qualitative approach and the type of research is field research. The data collection techniques used in this thesis are observation methods, in-depth interviews, and documentation studies. The collected data were then analyzed using interactive analysis techniques, which include data collection, data condensation, data presentation, and drawing conclusions. Furthermore, the data were analyzed using source triangulation and technique triangulation techniques. The results of this research are: 1) Public relations planning in involving community participation is: there are two types, namely routine work program planning (inviting parents, halalbihalal, commemorating Islamic holidays, and facilitating graduation ceremonies) and incidental work program planning (receiving visits, and communication with community leaders); 2) The implementation of public relations in involving community participation consists of various activities, all activities are carried out by involving internal and external communities.